Electric-acoustic stimulation in adults: localization and speech perception. (May 2014) - Incerti, Paola V; Ching, Teresa Y C; Cowan, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> This paper reports findings from a study that was aimed at investigating how best to prescribe devices that provide electric-acoustic stimulation. The localization and speech perception of adults who use electric-acoustic stimulation in one ear and acoustic amplification in the opposite ear were evaluated. Results indicated localization benefits when acoustic amplification was used in both ears. Systematic adjustments of the relative output and cross-over frequencies were implemented to determine the settings that optimized outcomes. Results from a case study indicated benefits for localization and speech perception when electric–acoustic stimulation in one ear was combined with a hearing aid in the opposite ear, after acoustic-to-electric levels and cross-over frequencies were optimized.